Investigasi pandangan guru terhadap integrasi pembelajaran berbasis proyek dengan Canva Magic Write untuk mendukung SDG 4 - Novasa Adiyani; Joko Priyana; Albokhary Alsnousi Othman Alhadeeri (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The Ministry of Education and Culture of Indonesia (Kemendikbud), through the 2013 Curriculum, emphasizes the development of 21st-century skills. Teachers, as educational initiators, are expected to equip students with the 4Cs: critical thinking and problem-solving, communication, collaboration, and creativity. To foster these skills, teachers are encouraged to implement student-centred teaching methods that focus on active learning rather than passive instruction. Project-Based Learning (PjBL) aligns with this approach, as it engages students in constructing knowledge and developing skills through meaningful, real-world projects. While PjBL emphasizes authentic learning tasks, Canva Magic Write facilitates digital creativity and linguistic expression, offering a complementary tool for enhancing writing instruction. This combination is to support SDG 4, quality education. This study aims to investigate English teachers’ views on implementing PjBL integrated with Canva Magic Write in teaching writing at the junior high school level. It also explores the challenges teachers face and the strategies they employ to overcome them. This qualitative case study involved English teachers with a minimum of two years of teaching experience. Data were collected through interviews and document analysis, then analysed using thematic analysis. The findings indicate that integrating Canva Magic Write with PjBL has excellent potential to enhance students' engagement, creativity, and writing quality. The study contributes to teachers’ education by highlighting the pedagogical value of combining PjBL with digital tools to support the development of 21st-century literacy.